EFFICACY OF VARIOUS METHODS OF NEUROMOTOR CORRECTIONAL TRAINING OF LOCOMOTIVE STEREOTYPE IN PATIENTS WITH SPASTIC DIPLEGIA FORM OF INFANTILE CEREBRAL PARALYSIS WITH THE MEANS OF «GRAVITON» DEVICE - N. Yu. Titarenko; A. V. Averkin; V. I. Dotsenko; V. D. Levchenkova; I. Ya. Politova; K. A. Semenova ("Paediatrician" Publishers LLC, 2013)
Aim: to compare efficacy of one course of reflex-lead device (RLD) at standard regimen and at regimen of temporary aggravation of pathological placing of the lower extremities during the training of patients with spastic diplegia form of infantile cerebral paralysis. Patients and methods: children aged from 8 to 12 years old with moderate spastic diplegia were included into the study. The initial pattern of locomotion was characterized by cnemial flexion in the knee joints (n =61); among them 30 patients were applied correctional regimen of RLD, in 31 patient the severity of pathological placing of the lower extremities was increased by the means of traction of RLD. Results: after the treatment course (consisting of 20 sessions in RLD), ambulation of the patients in the group of correctional regimen of RLD (n =30) was characterized by the less diversity, while in the group of training aggravation of the pathological position of the lower extremities (n =31) more significant partial normalization of kinetic pattern of the articular angles in the lower extremities was observed. Conclusions: standard correctional regimen of RLD is an optimal method of neuromotor correctional training, while training aggravation of the severity of pathological positions of the lower extremities has better effects on modulation of locomotive stereotype and should be used in order to correction of ambulance in patients with independent ability to move.